Analisis Kesalahan Gramatikal Pada Tulisan Mahasiswa Tentang Simple Present Tense: Studi Kasus Pada Mahasiswa Semester Satu Jurusan Bukan Bahasa Inggris Di Universitas PGRI Palangka Raya - Tutik Haryani (FKIP Universitas Palangka Raya, 2022)
This study is about gammatical errors in student’s writing of the simple present tense. This research was conducted at the University of PGRI Palangka Raya, especially for the first semester students of non-English study programs. The research process begins by making observations among students in applying the basic concepts of the simple present tense in daily activities. Before analyzing the research, the researcher conducted observations and written test on students. In observation, the researcher found that more than 50% of students could not understand the basic concepts of the simple present tense well. They often make some grammatical mistakes. The topic of this research is chosen based on the researcher's experience as an English teacher. Researcher often finds students' grammatical errors, especially in the simple present tense. The research objectives are formulated as follows: (1). To find out the types of grammatical errors made by the students in making simple present tense sentences (2).To find out the causes of grammatical errors made by the students. This study is qualitative research. The data collection technique is by doing written test. To collect the data, students are asked to write down their daily activities in English. After that, the data is analyzed. In this written test, there are 30 out of 40 students (75%) who can write simple present tense sentences correctly, somo other student still make errors gramatically. Errors that are mostly made by students are Omission errors, Addition Errors, Formation Errors, and ordering Errors. The causes of grammatical errors in student’s Writing are the first is Overgeneralization defined as a use of a grammar pattern strategy, available for use in new situations, and the second is Ignorance of rules restrictions include intralingual errors related to analogies.